The Frame and Name of the Medical Treatment and their Influence on Health Decisions - Damnjanović, Kaja; Ilić, Sandra; Teovanović, Predrag (Psihološka istraživanja, 2019)
Decisions about one’s own health range from everyday and easy ones, such as taking a vitamin pill, to those made in the situations of life-threatening diseases. When it comes to choosing treatments, patients have difficulty understanding statistical information about the possible outcomes of alternative treatments such as probabilities and risks. These challenges are especially important in the context of the shared decision-making. The aim of this study was to examine influence of the labelling of the treatment in risky choice decision tasks. The risky choice framing effect (FE) pertains to the systematic preference reversal because different aspects of formally identical situations are emphasized. In the present study, the participants made a forced choice between a non-risky and risky treatment presented in terms of gains and losses. In the first condition, surgery was the risky option and in the second it was the radiation. In the third condition, the treatments’ labels were replaced with ’A’ and ’B’. Chi-square tests revealed a significant difference in proportions of risky choices between the three conditions. The FE was registered only in the first and the second condition, and it was moderate and strong, respectively. When choosing between surgery and radiation, participants’ choices were indeed influenced by the naming of the treatment, but not exclusively - they generally preferred surgery, and when it was offered in terms of losses, they preferred it even more.
Keywords: health decision; shared decision making; risky choice; framing effect; medical treatment; surgery; radiation; prospect theory; fuzzy-trace theory; patient